Comparative study of copper oxidation protection with graphene and hexagonal boron nitride. (January 2021) - Scardamaglia, Mattia; Boix, Virginia; D'Acunto, Giulio; Struzzi, Claudia; Reckinger, Nicolas; Chen, Xin; Shivayogimath, Abhay; Booth, Tim; Knudsen, Jan
Abstract: The use of protective barriers to isolate a metal surface from an aggressive environment is a common way to inhibit its degradation. We used ambient pressure x-ray photoelectron spectroscopy to assess in real time the evolution of the copper surface and the contextual protective action of 2D material coatings (graphene and hexagonal boron nitride) towards copper oxidation. In an isobaric experiment with 2 mbar of oxygen, the bare copper oxidizes near room temperature, while both 2D materials can retard the onset temperature for the first oxidation of copper by more than 120 °C. However, their protection mechanism is different: boron nitride behaves more straightforwardly, forming an effective barrier to copper oxidation until it is etched away at high temperatures, leading to a rapid oxidation to cuprous and then cupric oxide. On the other hand, graphene reveals to be a more interesting playground underneath oxygen intercalates and begins a slower undercover oxidation of copper. The coexistence between graphene and cuprous oxide, not observed in boron nitride, protects the copper from further oxidation to cupric oxide. Graphical abstract: Image 1